A review report of a decade's trends in bullying in selected academic and media publications - Brown, Tarryn (My University, 2015)
Bullying is a worldwide phenomenon that is receiving increasing attention worldwide. Most of the research on bullying has grown from the seminal work by Dan Olweus in the 1970s yet as society and technology has advanced so has bullying. The emergence of cyberbullying in recent literature is one of the trends that has developed in bullying discourse. This research aimed to explore this and other trends in bullying research over a ten year period (2003-2012), comparing South African, British, and international journals as well as South African and British media. Focus was given to the major themes that emerged in the various data sources, and the quantitative trends that developed from these themes. Of particular interest was how bullying is socially constructed through various media. Using a sequential exploratory design of mixed methods where the qualitative phase of analysis preceded the quantitative phase, 1047 articles were gathered and analysed. Of these, 231 articles were collected from the research journals; 431 from the South African media and 385 from the British media. Ten major themes were identified across all data sources, the results tabulated and quantified. The results indicated that research on bullying has followed specific trends over the past ten years which differ between South Africa and Britain. The trends appeared to be independent of media reports, yet research does draw on media for direction occasionally. Bullying has been socially constructed differently in South Africa and Britain, and the research suggested that public understanding may be more strongly linked to media than to journal articles. The findings therefore pointed to the fact that researchers in the field need to work on making their results known in order to shape the public’s understanding of a phenomenon affecting many children globally.
A research report submitted to the Faculty of Humanities, University of the Witwatersrand, Johannesburg, in partial fulfillment of the requirements for the degree of Master of Arts in Educational Psychology May 2014